The impact of trisomy 21 on treatment modalities and outcome in adults with congenital heart disease in Switzerland. (1st November 2018) - ,; Johannes, Judith; Greutmann, Matthias; Tobler, Daniel; Bouchardy, Judith; Stambach, Dominik; Wustmann, Kerstin; Schwitz, Fabienne; Schwerzmann, Markus
Abstract : Trisomy 21 (T21) is associated in 40–45% of cases with heart defects, most commonly shunt lesions. These defects, if not repaired, can lead to irreversible shunt‐induced pulmonary hypertension (i.e. Eisenmenger syndrome [ES]). In ES patients, intracardiac repair is no longer possible, but selective pulmonary vasodilators may increase exercise capacity and improve prognosis. This study aimed to estimate the prevalence of cardiac defects and ES in adult T21 patients and to assess the impact of T21 on treatment modalities and outcome in ES patients. A questionnaire was sent to 6906 Swiss physicians inviting them to indicate the number of adults with T21 under their care (survey report). We also analyzed all adults with ES (with and without T21) included in the Swiss Adult Congenital HEart disease Registry (SACHER) and studied the impact of T21 on the use of selective pulmonary vasodilators and survival. In the survey, 348 physicians cared for 695 adult T21 patients. Overall, 24% of T21 survey patients were known to have a cardiac defect, one in four with a defect had developed ES and 13% of those with ES were on specific pulmonary vasodilators. In SACHER, ES was present in 2% of adults with congenital heart disease and selective pulmonary vasodilators were used in 68% of ES patients with T21. In SACHER, survival during follow‐up was worse with higher nt‐proBNP levels (hazard ratio [HR] = 1.15 per 1000 units, 95% confidence interval [CI] = 1.02–1.29) and lower left ventricular ejection fraction (HR = 1.07 per percent decrease, 95% CI = 1.01–1.13). Age at inclusion and T21 did not affect survival. The prevalence of cardiac defects in adults with T21 in Switzerland is half the prevalence in children. T21 is over‐represented among adults with ES. Raised awareness of the therapeutic options for T21 patients with ES is warranted.